Biallelic CHP1 mutation causes human autosomal recessive ataxia by impairing NHE1 function. (February 2018) - Mendoza-Ferreira, Natalia; Coutelier, Marie; Janzen, Eva; Hosseinibarkooie, Seyyedmohsen; Löhr, Heiko; Schneider, Svenja; Milbradt, Janine; Karakaya, Mert; Riessland, Markus; Pichlo, Christian; Torres-Benito, Laura; Singleton, Andrew; et al.
Abstract : Objective: To ascertain the genetic and functional basis of complex autosomal recessive cerebellar ataxia (ARCA) presented by 2 siblings of a consanguineous family characterized by motor neuropathy, cerebellar atrophy, spastic paraparesis, intellectual disability, and slow ocular saccades. Methods: Combined whole-genome linkage analysis, whole-exome sequencing, and focused screening for identification of potential causative genes were performed. Assessment of the functional consequences of the mutation on protein function via subcellular fractionation, size-exclusion chromatography, and fluorescence microscopy were done. A zebrafish model, using Morpholinos, was generated to study the pathogenic effect of the mutation in vivo. Results: We identified a biallelic 3-bp deletion (p.K19del) in CHP1 that cosegregates with the disease. Neither focused screening for CHP1 variants in 2 cohorts (ARCA: N = 319 and NeurOmics: N = 657) nor interrogating GeneMatcher yielded additional variants, thus revealing the scarcity of CHP1 mutations. We show that mutant CHP1 fails to integrate into functional protein complexes and is prone to aggregation, thereby leading to diminished levels of soluble CHP1 and reduced membrane targeting of NHE1, a major Na + /H + exchanger implicated in syndromic ataxia-deafness. Chp1 deficiency in zebrafish, resembling the affected individuals, led to movement defects, cerebellar hypoplasia, and motor axon abnormalities, which were ameliorated by coinjection with wild-type, but not mutant, human CHP1 messenger RNA. Conclusions: Collectively, our results identified CHP1 as a novel ataxia-causative gene in humans, further expanding the spectrum of ARCA-associated loci, and corroborated the crucial role of NHE1 within the pathogenesis of these disorders.